Overall acceptability and shelf life evaluation of cakes produced from wheat, cocoyam, plantain, and Bambara nut composite flours - Eunice Kanayo Agidi; Diana Oritsegbubemi Arubayi; Juliana Ego Azonuche; Omolara Bosede Ogbonyomi; Obiajulum Vivian Onyenokulu (PT. Pena Produktif Kreatif, 2026)
Cakes are widely consumed bakery products typically made from wheat flour, yet dependence on imported wheat can create economic and nutritional challenges in many developing countries. This study evaluated the acceptability and shelf life of cakes produced from composite flours based on wheat, cocoyam, plantain, and Bambara nut (WCPB1–WCPB6) compared with 100% wheat flour (WF) as control. Cakes were prepared and evaluated by 15 panelists using a 9-point hedonic scale, and shelf life attributes were monitored over 20 days at 4-day intervals. All samples were highly acceptable during the initial storage period, and sensory scores generally remained within the acceptable range throughout storage, with WF tending to receive the highest ratings. Statistical analysis showed significant differences in taste among formulations at later storage times (p ≤ 0.05), whereas other sensory attributes were largely comparable. Although quality declined and mold growth appeared after prolonged storage, several composite-flour cakes remained above the sensory cut-off for acceptability at day 20. These findings indicate that cocoyam, plantain, and Bambara nut composite flours can partially substitute wheat in cake production without compromising product quality, while supporting the utilization of indigenous crops and contributing to food and nutrition security.